Truffle Species Discrimination Based on Their Chemical Composition, Chromaticity Coordinates and Antioxidant Capacity - Cristina Valencia-Sullca; Anja Rakotondramavo; Catherine Verret; Jean-Philippe Blondeau; Sullivan Renouard (Polish Journal of Food and Nutrition Sciences)
Some edible truffle species are more sought after and expensive than others while they have a similar colour and appearance. This therefore leads to high risk of fraud. To prevent these frauds, this study proposes to explore the chemical composition and antioxidant capacity to discriminate the six-truffle species encountered in France. To achieve this, infrared spectrometry analysis, chromaticity measures and atomic absorption analysis were performed on dehydrated truffle powder as well as antioxidant capacity (ABTS and CUPRAC assays) and total phenolic content analyses were performed for truffle aqueous ethanol extracts. Infrared spectrometry analysis provided results allowing to discriminate the six-truffle species using a chitin/chitosan ratio (1,659 cm -1 /1,627 cm -1 ) determined in the range of 0.75 to 0.93 or a β/α-glucan ratio (889 cm -1 /850 cm -1 ) in the range from 1.50 to 1.81. Colour coordinates, including L*, a* and b* values, ranged from 20.56 to 36.35, 1.62 to 4.23 and 2.78 to12.9, respectively, and differed significantly between species. Truffle calcium and magnesium content was 2.62–0.48 mg/g dry weight and -0.91–0.21 mg/g dry weight, which also differentiated truffle species. Total phenolic content and antioxidant capacity analyses allowed to discriminate most of the six-truffle species but not each of the species. Thus, biophysical approaches and, to a lesser extent, the antioxidant activity assays, and total phenolic content are credible means of identifying truffle species found in France.